A NEW LATE PLEISTOCENE MAMMAL LOCALITY FROM WESTERN CRETE - Iliopoulos, G.; Eikamp, H.; Fassoulas, C. (Bulletin of the Geological Society of Greece, 2010)
During the last five years systematic explorations of the Natural History Museum of Crete have added more than 20 Pleistocene fossil localities around Crete to the catalogue of the over 70 already known on the Island. The new localities are distributed in all four prefectures of Crete. The most important of these is the newly discovered site of Koutalas at Cape Drepano in Western Crete. The fossil remains are found in two levels and in red cemented clays of a collapsed cave. In the upper level a rich assemblage of micromammal, bird and large mammal remains has been discovered. The large mammals consist of dwarf hippopotamus (Hippopotamus creutzburgi) and elephants (Elephas sp.). A partly articulated skeleton (vertebral column, mandible and few long bones) of a dwarf hippo has been found next to a deciduous molar of an elephantid, indicating that the two taxa probably coexisted. The micromammal remains belong to the giant Cretan mouse Kritimys catreus. Therefore, the age of the assemblage is dated to the Kritimys catreus zone and thus to the late Middle Pleistocene. In the lower level scattered remains of deers, birds and micromammals have been identified, and their age is most likely younger than that of the upper level.